2020
DOI: 10.1109/jeds.2020.2966799
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Switching Properties in TaOx Memristors Using Diffusion Limiting Layer for Synaptic Learning

Abstract: To move towards a new generation powerful computing system, brain-inspired neuromorphic computing is expected to transform the architecture of the conventional computer, where memristors are considered to be potential solutions for synapses part. We propose and demonstrate a novel approach to achieve remarkable improvement of analog switching linearity in TaN/Ta/TaO x /Al 2 O 3 /Pt/Si memristors by varying Al 2 O 3 layer thickness. Presence of the Al 2 O 3 layer is confirmed from the Auger Electron Spectroscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 29 publications
0
24
0
Order By: Relevance
“…The formation of interfacial layer at the bottom interface may help to induce analog behavior in memristor devices. 21 However, in this work, we found that such technique may not sufficient to achieve both analog set and reset. TaOx was employed as a switching layer of the CBRAM device due to its compatibility in CMOS processes.…”
mentioning
confidence: 69%
“…The formation of interfacial layer at the bottom interface may help to induce analog behavior in memristor devices. 21 However, in this work, we found that such technique may not sufficient to achieve both analog set and reset. TaOx was employed as a switching layer of the CBRAM device due to its compatibility in CMOS processes.…”
mentioning
confidence: 69%
“…During the past decade, several transition-metal oxides such as ZnO, ZrO 2 , , HfO 2 , NiO, Sm 2 O 3 , Eu 2 O 3 , SnO 2 , WO 3 , , and TiO 2 have been studied rigorously for the memristive applications. Among them, TaO x has gained broader attention in-between numerous researchers because of its promising reliability, high performance, and neural network applications. Nevertheless, the reliability and performance of the flexible and transparent memristor are still inadequate to achieve a commercial level for portable and wearable electronics . Moreover, memristors are prone to degrade under ultraviolet (UV) irradiation, hindering their realization for wearable electronics; huge efforts have been made to understand their mechanism and mitigate this issue. In this work, we design high-performance TaO x -based flexible and transparent memristor devices by inserting an ultrathin AlN layer accomplishing high reliability toward extreme UV irradiation that offers good potential for outdoor and aerospace applications.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, TaO x has gained broader attention in-between numerous researchers because of its promising reliability, high performance, and neural network applications. Nevertheless, the reliability and performance of the flexible and transparent memristor are still inadequate to achieve a commercial level for portable and wearable electronics . Moreover, memristors are prone to degrade under ultraviolet (UV) irradiation, hindering their realization for wearable electronics; huge efforts have been made to understand their mechanism and mitigate this issue. In this work, we design high-performance TaO x -based flexible and transparent memristor devices by inserting an ultrathin AlN layer accomplishing high reliability toward extreme UV irradiation that offers good potential for outdoor and aerospace applications. In addition, our design not only has the potential for wearable electronic applications but also for touch panels/display-embedded systems as the device structure is fabricated on the indium tin oxide (ITO)-coated substrate.…”
Section: Introductionmentioning
confidence: 99%
“…Various transport processes in the oxide-based RRAM structures can be responsible for the resistive switching effect depending on the material stack and a fabrication method, e.g., trap-assisted tunneling, Poole-Frenkel emission, SILC, or hopping transport [9]. Many oxide materials exhibiting resistive switching (RS) have been examined in recent years, including HfO 2 , TiO 2 , and Ta 2 O 5 [10][11][12][13][14][15][16][17][18][19]. Silicon oxide has also been tested as a potential candidate for an RS layer in CBRAM and OxRAM devices [20][21][22][23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%